1992
DOI: 10.1002/j.1460-2075.1992.tb05181.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyr721 regulates specific binding of the CSF-1 receptor kinase insert to PI 3′-kinase SH2 domains: a model for SH2-mediated receptor-target interactions.

Abstract: Efficient binding of active phosphatidylinositol (PI) 3′‐kinase to the autophosphorylated macrophage colony stimulating factor receptor (CSF‐1R) requires the noncatalytic kinase insert (KI) region of the receptor. To test whether this region could function independently to bind PI 3′‐kinase, the isolated CSF‐1R KI was expressed in Escherichia coli, and was inducibly phosphorylated on tyrosine. The tyrosine phosphorylated form of the CSF‐1R KI bound PI 3′‐kinase in vitro, whereas the unphosphorylated form had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
170
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(180 citation statements)
references
References 50 publications
10
170
0
Order By: Relevance
“…In agreement with previous reports (Reedijk et al, 1992;Joos et al, 1996), such speci®c binding was indeed observed, provided that the GST-KI-Fms protein was phosphorylated ( Figure 3c). As expected, some Grb2 was detected in the GST-pY-KI-Fms fraction (van der Geer and Hunter, 1993).…”
Section: Gst-ki-fms and Gst-ct-fms Fusion Proteins Associate With Grbsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous reports (Reedijk et al, 1992;Joos et al, 1996), such speci®c binding was indeed observed, provided that the GST-KI-Fms protein was phosphorylated ( Figure 3c). As expected, some Grb2 was detected in the GST-pY-KI-Fms fraction (van der Geer and Hunter, 1993).…”
Section: Gst-ki-fms and Gst-ct-fms Fusion Proteins Associate With Grbsupporting
confidence: 93%
“…Several autophosphorylation sites of the Fms molecules have been mapped. These include Y543 in the JX domain (Joos et al, 1996), Y696, Y705, and Y720 (corresponding to Y697, Y706 and Y721 in the mouse c-Fms) in the KI domain, and Y807 in the K2 domain (Tapley et al, 1990;van der Geer and Hunter, 1990Roussel et al, 1990;Reedijk et al, 1992;Trouliaris et al, 1995a,b;Joos et al, 1996). Which are the cellular proteins that bind to these autophosphorylation sites?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the best studied sites is that which mediates interactions with the SH2 domains of the p85 subunit of the PI 3-kinase. This enzyme has been shown to associate with the human PDGF P-receptor via tyrosines 740 and 75 1, which lie in the kinase insert region of this receptor (Fantl et al, 1992;Kashishian et al, 1992); with the murine CSF-1 receptor via tyrosine 721 (Reedijk et al, 1992); with tyrosine 315 of polyoma middle T antigen in the mT/pp60C-S" transforming complex (Talmage et al, 1989); and with several phosphorylated tyrosines on the insulin receptor substrate, IRS-1 Yonezawa et al, 1992). All of these tyrosines lie within the consensus sequence YxxM (where x can be a wide range of possible residues).…”
Section: Sh2 Domain-specific Binding Sitesmentioning
confidence: 99%
“…It is not known whether this results from either the lack of PLC␥ activity or from the different location, at the C-terminus sequence of the SH2-p85-PI3Ј kinase binding site (Tyr 958) of FLT3 64 compared to other class III RTK. [65][66][67] Alternatively, because this phosphorylated tyrosine residue is also a docking site for the GRB2 adaptator molecule (Beslu et al manuscript in preparation), competitive association could titrate this site for one of the substrate and hide its associated function.…”
Section: Figurementioning
confidence: 99%